2015
DOI: 10.7763/ijssh.2015.v5.495
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Social Networks Sites (SNSs) among University Students: How Far do They Learn

Abstract: Abstract-The study investigated the pedagogical affordances of SNS and its relationship on student engagement. A sample of 300 students responded to this quantitative research using a self constructed questionnaire. The hypothesized model has been tested to determine the relationships between pedagogical affordances and student engagement. This model underpins the theory of constructivist of interactions that promote learning; connectivity and collaboration through Web 2.0 technology. Using Multiple Regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Some of the reasons behind teachers social media posts and interactions with their students were as followed gain a positive attitude toward the teacher and lecture (Akkoyunlu, Dağhan and Erdem, 2015;Bridges, 2009), to improve the relationship between them (Akiti, 2012;Couillard, 2009;Kamnoetsin, 2014;Kırksekiz, 2013;Montoneri, 2015) to provide students information about school and lecture related topics and increase students' academic performance. Also as a result of teachers self-disclosure on social media it was determined that an emotional bond formed between the teacher and the student and this increased their trust and closeness (Eke, Omekwu and Odoh, 2014;Haeger, Wang and Lorenz, 2014;Kuzu, 2014;Lane, 2013;Lane and Lewis, 2013), they developed positive attitudes toward the lecture and teacher (Akkoyunlu, Dağhan and Erdem, 2015;Bridges, 2009;Sorenson, 1989;Tuncel, 2007), their communication with the teacher increased (Ha and Shin, 2009;Hassan and Landani, 2015;Menteşe, 2013), their interest to the course increased (Cayanus, 2004) content of the lecture became more understandable (Cayanus and Martin, 2008), students' participation increased (Lam, 2012) and their motivation and success increased (Atkins, 2010;Mazer and Hosek, 2012). From these it is seen that the reason behind teacher self-disclosure and the effects it has on students' corresponds with the previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the reasons behind teachers social media posts and interactions with their students were as followed gain a positive attitude toward the teacher and lecture (Akkoyunlu, Dağhan and Erdem, 2015;Bridges, 2009), to improve the relationship between them (Akiti, 2012;Couillard, 2009;Kamnoetsin, 2014;Kırksekiz, 2013;Montoneri, 2015) to provide students information about school and lecture related topics and increase students' academic performance. Also as a result of teachers self-disclosure on social media it was determined that an emotional bond formed between the teacher and the student and this increased their trust and closeness (Eke, Omekwu and Odoh, 2014;Haeger, Wang and Lorenz, 2014;Kuzu, 2014;Lane, 2013;Lane and Lewis, 2013), they developed positive attitudes toward the lecture and teacher (Akkoyunlu, Dağhan and Erdem, 2015;Bridges, 2009;Sorenson, 1989;Tuncel, 2007), their communication with the teacher increased (Ha and Shin, 2009;Hassan and Landani, 2015;Menteşe, 2013), their interest to the course increased (Cayanus, 2004) content of the lecture became more understandable (Cayanus and Martin, 2008), students' participation increased (Lam, 2012) and their motivation and success increased (Atkins, 2010;Mazer and Hosek, 2012). From these it is seen that the reason behind teacher self-disclosure and the effects it has on students' corresponds with the previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was planned to develop a scale for teachers to disclose themselves to their students through social media. In this respect, the literature on teachers" use of social media and teacher-student interaction on social media was reviewed (Acar & Yenmiş, 2014;Alican & Saban, 2013;Arthur & Bostedo-Conway, 2012;Atkins, 2010;Bridges, 2009;Cayanus, 2004;Cayanus & Martin, 2004;Cayanus & Martin, 2008;Cayanus, Martin & Goodboy, 2009;Çakmak & Arap, 2013;Dawson, 2008;Eke, Omekwu & Odoh, 2014;Eugenia & Wong, 2013;Farani & Fatemi, 2014;Ha & Shin, 2014;Haeger, Wang & Lorenz, 2014;Hassan & Landani, 2015;Hosek & Thompson, 2009;Hurt et al, 2012;Irwin, Desbrow & Leveritt, 2012;Ili, 2013;Junco, Heiberger & Loken, 2011;Kırksekiz, 2013;Kuzu, 2014;Lam, 2012;Lane, 2013;Lane & Lewis, 2013;Liccardi, 2007;Mazer, et al, 2007;Mazer & Hosek, 2012;Munoz & Towner, 2009;Nkhoma et al, 2015;Sang, 2014;Saylag, 2012;Smith, 2015;Tarantino, McDonough & Hua, 2013;Tarawneh, 2014;Tiryakioğlu & Erzurum, 2011;Togay et al, 20...…”
Section: Development Of the Data Collection Toolmentioning
confidence: 99%
“…The interesting finding come out from this study that majority of the students believe for using maximum time on SNSs do not affect their academic performance. hassan & Landani 20 found that most of the students use SNSs less than an hour daily. They also reported that 'SNS allow students not only to expand relationships beyond the classroom but also to improve their communication skills'.…”
Section: Usage Of Social Networking Sites Throughoutmentioning
confidence: 99%